ANALISIS PERAN LEMBAGA AMIL ZAKAT INFAQ DAN SHODAQOH “LAZISNU” CABANG NGANJUK DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Fahdina Naila Rohmah; Aan Nasrullah (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
Poverty is a great danger for humanity and not a few human beings who fall into civilization only because of poverty. As a solution to alleviating poverty that is vulnerable to this country, the government with various programs implemented is trying to be able to reduce the poverty chain. One potential funding source is zakat, infaq and shodaqoh funds, both managed by the Amil Zakat Institute (LAZ). The purpose of this study is to explain the role of the Amil Zakat Infaq Shodaqoh